2021
DOI: 10.1111/eip.13155
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches and outcome trajectories for youth with high‐risk opioid use: A narrative review

Abstract: Aim First use of opioids often happens in adolescence and an increasing number of opioid overdoses are being reported among youth. The purpose of this narrative review was to present the treatment approaches for youth with high‐risk opioid use, determine whether the literature supports the use of opioid agonist treatment among youth and identify evidence for better treatment outcomes in the younger population. Methods A search of the literature on PubMed using MeSH terms specific to youth, opioid use and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…Current guidelines to treat opioid use disorder (OUD) among youth include a combination of pharmacological (e.g., OAT) and psychosocial (e.g., cognitive behavioral therapy) interventions, as well as family-oriented treatments and long-term recovery services [30]. Yet, youth experience a number of barriers when trying to access these services, including age-based restrictions [31,32], service provider hesitancy to prescribe OAT to youth [33,34], a lack of confidentiality and privacy [32,35], and limited youth-friendly service options [32,34,36,37], which may explain why youth are less likely to access or remain engaged in opioid use treatments/services compared to adults [38][39][40][41]. Several qualitative studies have found that youth often feel unsafe accessing adult-oriented harm reduction services (e.g., safe consumption sites, OAT), which can prevent them from accessing life-saving programs [32,34,42].…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines to treat opioid use disorder (OUD) among youth include a combination of pharmacological (e.g., OAT) and psychosocial (e.g., cognitive behavioral therapy) interventions, as well as family-oriented treatments and long-term recovery services [30]. Yet, youth experience a number of barriers when trying to access these services, including age-based restrictions [31,32], service provider hesitancy to prescribe OAT to youth [33,34], a lack of confidentiality and privacy [32,35], and limited youth-friendly service options [32,34,36,37], which may explain why youth are less likely to access or remain engaged in opioid use treatments/services compared to adults [38][39][40][41]. Several qualitative studies have found that youth often feel unsafe accessing adult-oriented harm reduction services (e.g., safe consumption sites, OAT), which can prevent them from accessing life-saving programs [32,34,42].…”
Section: Introductionmentioning
confidence: 99%
“…These medications are effective in reducing symptoms of opioid withdrawal and craving, overdose risk, mortality, and morbidity (Mattick et al, 2009(Mattick et al, , 2014Sordo et al, 2017;Strang et al, 2020). Although empirical studies on the effectiveness of OAT in youth are limited, emerging research suggests it is beneficial (Camenga et al, 2019;Pilarinos et al, 2022;Westenberg et al, 2021) Addictions, 2018;Krausz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These medications are effective in reducing symptoms of opioid withdrawal and craving, overdose risk, mortality, and morbidity (Mattick et al, 2009, 2014; Sordo et al, 2017; Strang et al, 2020). Although empirical studies on the effectiveness of OAT in youth are limited, emerging research suggests it is beneficial (Camenga et al, 2019; Pilarinos et al, 2022; Westenberg et al, 2021), and clinical guidance recommends its delivery to youth (American Academy of Pediatrics Committee On Substance Use and Prevention, 2016; British Columbia Centre on Substance Use, B.C. Ministry of Health, & B.C.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of this range of interventions remains largely understudied among youth using opioids [ 14 , 23 , 24 ]. Emerging evidence also suggests that youth encounter barriers to seeking and remaining in opioid treatment services [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%